Evaluation of a new implant for Tibial Tuberosity Transposition in dogs: An ex vivo study - Gabriel Rampanelli; Olicies da Cunha; Anderson Luiz de Carvalho; Cássio Ricardo Auada Ferrigno; Camila Aparecida Luiz; Laura Ayala Lazarotto; Lucas Dill Mocellin; João Pedro Cosmo Machado; Fernando Lunardelli (PLoS ONE, 2025)
The present study aims to describe and evaluate the effectiveness and potential applicability of a new implant designed to transpose the tibial tuberosity. The implant consists of a customized plate for fixation on the tibia, containing a hole for the insertion of a transposition screw in the tibial tuberosity. Computed tomography was performed on 21 cadaveric canine tibias to plan the surgical technique and calculate the desired transposition. Subsequently, an osteotomy of the tibial tuberosity was performed, extending 60% of the lateral cortex and 80% of the medial cortex to maintain a bone bridge between the tibial shaft and the osteotomized segment. After the osteotomy, the implant was fixed to the tibia, and the tibial tuberosity was transposed slowly and gradually using the transposition screw. The samples underwent radiographic evaluation and manual palpation following the application to detect tibial crest fractures. The plate’s shape adequately fit the medial surface of the tibia, and the implant was effective in promoting a slow and gradual transposition in canine cadavers without the need for an additional surgical device to perform the maneuver. The implant proved to be effective in achieving the desired transposition in a progressive, gradual, and slow manner.